Menelusuri pendemokrasian di Malaysia: impak terhadap pencapaian integrasi nasional / Jazimin Zakaria and Sity Daud - Zakaria, Jazimin; Daud, Sity (2018)
This article is the result of a study carried out on the level of national integration within the context of democracy. For a multi-ethnic country, achieving a full democracy is invariably a formidable challenge. Social exclusivity and surrounding factors such as socio-economy and socio-politics appear to among the major hurdles against the effort to realize a full national integration, more so countries used to be under colonial yoke for a considerable time. Malaysia, as one of those countries, eventually accepts the impact of colonialism that, among others, has inadvertently changed much of its social landscape. However, the protracted bargaining process between the ethnics has helped to bring about political stability to the country for many years. Yet, globalization still has managed to induce changes within the system of democracy so much so that it has significantly affected the level of national integration of the society. As such, this qualitative study seeks to identify key problems that stand in the way of full national integration that is in congruence with the principles of democracy. Based on the analysis done over primary and secondary data obtained, this study argues that liberal democracy had impacted national integration through, among others, ‘soft assimilation method’ seen as more than capable of reinforcing unity among multi-ethnics’ society of Malaysia.